2014
DOI: 10.1007/s11999-014-3619-5
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive versus Open Posterior Lumbar Interbody Fusion: A Systematic Review

Abstract: BackgroundAlthough conventional open posterior lumbar interbody fusion (open PLIF) is efficacious in management of lumbar spinal instability, concerns exist regarding lengthy hospital stays, blood loss, and postoperative complications. Minimally invasive posterior lumbar interbody fusion (MIS PLIF) may be able to address these concerns, but the research on this topic has not been systematically reviewed. Questions/purposes We performed a systematic review to determine whether MIS PLIF or open PLIF results in (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 20 publications
1
31
1
1
Order By: Relevance
“…Additional studies in a prospective multicentered large population will be needed to further define the risk factor of reoperation of the surgical treatment of DS. Favorable clinical outcomes and reoperation rates for less-invasive decompression surgery for Meyerding Grade 1 DS were recently reported [22][23][24][25]; this less-invasive surgery might reduce the reoperation rate for decompression surgery for this condition.…”
Section: Discussionmentioning
confidence: 87%
“…Additional studies in a prospective multicentered large population will be needed to further define the risk factor of reoperation of the surgical treatment of DS. Favorable clinical outcomes and reoperation rates for less-invasive decompression surgery for Meyerding Grade 1 DS were recently reported [22][23][24][25]; this less-invasive surgery might reduce the reoperation rate for decompression surgery for this condition.…”
Section: Discussionmentioning
confidence: 87%
“…Currently, the minimally invasive (MI) lumbar spinal fusion techniques including MI posterior lumbar interbody fusion [6], MI transforaminal lumbar interbody fusion [7, 8], MI posterolateral lumbar fusion, MI lateral lumbar fusion [9], MI oblique lumbar interbody fusion, and MI anterior lumbar interbody fusion. The posterior approach permits the decompression and discectomy directly and does not have complications of vessel, hypogastric sympathetic plexus, and ureter injury, which may be caused by anterior approach [10–12], and is most widely used nowadays [13].…”
Section: Introductionmentioning
confidence: 99%
“…A more acceptable concept of minimal invasive surgery (MIS) could be observed without providing comprehensive information regarding the potential risks. Part of recent meta-analysis also concluded that better benefit could be obtained when performed in specialized centers by experienced surgeons [113] . A consensus of opinion in the literature concerning the growing number of lumbar spine surgeries would highlight the need for further improvement that would maximize clinical outcomes.…”
Section: Methodsmentioning
confidence: 99%